2016
DOI: 10.1063/1.4939520
|View full text |Cite
|
Sign up to set email alerts
|

Methane dissociation on Pt(111): Searching for a specific reaction parameter density functional

Abstract: The theoretical description of methane dissociating on metal surfaces is a current frontier in the field of gas-surface dynamics. Dynamical models that aim at achieving a highly accurate description of this reaction rely on potential energy surfaces based on density functional theory calculations at the generalized gradient approximation. We focus here on the effect that the exchange-correlation functional has on the reactivity of methane on a metal surface, using CHD 3 + Pt(111) as a test case. We present new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 111 publications
(206 reference statements)
7
67
0
Order By: Relevance
“…Nevertheless, high quality results can already be obtained by judiciously choosing the set up for running AIMD. Nattino et al, for instance, investigated methane dissociative chemisorption on Pt(111) and used a 3 × 3 surface unit‐cell slab with 5 atomic layers to model the surface. These 45 platinum atoms were proven to be enough to capture the active effects of the lattice motion which were most important in dissociating the molecule.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, high quality results can already be obtained by judiciously choosing the set up for running AIMD. Nattino et al, for instance, investigated methane dissociative chemisorption on Pt(111) and used a 3 × 3 surface unit‐cell slab with 5 atomic layers to model the surface. These 45 platinum atoms were proven to be enough to capture the active effects of the lattice motion which were most important in dissociating the molecule.…”
Section: Applicationsmentioning
confidence: 99%
“…The authors of Ref. [ ] investigated in detail a number of issues, including the dependence of the reaction probabilities on the initial vibrational state of the molecule, its rotational alignment, and the temperature of the surface. They further performed a thorough comparison with available experimental results at a quantitative level, thereby demonstrating the power of this methodology.…”
Section: Applicationsmentioning
confidence: 99%
“…25,26 For gas-surface reactions, Perdew, Burke and Ernzerhof (PBE) 27 and Perdew Wang 91 (PW91) 28 typically underestimate E b and Revised PBE (RPBE) 29 tends to overestimate E b . 26,[30][31][32][33][34][35][36] Combining these to make an SRP functional can produce chemically accurate results for gas-surface reactions, as was first demonstrated by mixing the PW91 28 and RPBE 29 functionals for H 2 on Cu(111) 26,37 and Cu(100). 30 We have also demonstrated that an SRP exchange correlation functional can be used to reproduce the experimental sticking coefficients for CHD 3 on Ni(111) for both molecules prepared with a quantum of C-H stretch vibration and those without vibrational excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations were performed using a plane-wave pseudopotential code named ''Simulation tool for Atom TEchnology (STATE)''. 12 Since the vdW interaction is important to describe the adsorption and chemical reaction of inert molecules, 13 we compare the Perdew-Burke-Ernzerhof (PBE) results with those obtained using vdW density functionals (vdW-DFs), i.e., the original vdW-DF (vdW-DF1), 14 optB86b-vdW, 15 and rev-vdW-DF2 16 functionals as implemented in the STATE code. 17 We also included the dispersion correction proposed by Grimme with PBE (PBE-D2).…”
mentioning
confidence: 99%